Parenting Styles and Eating Behaviors Among Stunted Toddlers - Hervinda Rahma Setia; Shofa Nur Fauzah; Eni Suhaeni; Siti Maria Ulfah (Jurnal Kebidanan dan Kesehatan Tradisional, 2026)
ABSTRACT Background: Stunting remains a significant public health challenge in Indonesia, affecting 21.6% of children under five. While nutritional interventions are commonly implemented, the role of parenting styles in shaping eating behaviors among stunted children requires further investigation. This study explored how different parenting approaches relate to eating behaviors in stunted toddlers. Methods: A cross-sectional study was conducted using a consecutive sampling technique, involving 132 mothers with stunted toddlers aged 24–59 months at Kalijaga Permai Community Health Center, Cirebon City, between February and May 2025. Parenting styles were measured using the Parenting Styles Four Factor Questionnaire (PS-FFQ), while eating behaviors were assessed through a validated 6-item questionnaire. Spearman’s rank correlation was applied to analyze the relationships between parenting styles and eating behaviors. Results: Findings revealed that authoritarian parenting was most common (38.7%), followed by democratic (26.5%), permissive (25.0%), and uninvolved (9.8%) parenting styles. Nearly seven out of ten children (68.2%) exhibited problematic eating behaviors. Democratic parenting demonstrated the strongest positive relationship with healthy eating patterns (r=0.681, p<0.001). In contrast, authoritarian parenting showed a moderate negative association (r=-0.428, p<0.001), while permissive parenting displayed a weak negative correlation (r=-0.215, p=0.013). Uninvolved parenting showed no significant relationship with eating behaviors (r=-0.013, p=0.885).  Conclusion: Parenting styles are meaningfully associated with eating behaviors among stunted toddlers, with democratic parenting showing the strongest connection to healthier eating patterns. These findings suggest that stunting prevention programs should integrate parenting education focused on responsive feeding practices alongside traditional nutritional interventions.